2017
DOI: 10.1159/000485401
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TIMP3 Protects Against Cardiac Ischemia/Reperfusion Injury by Inhibiting Myocardial Apoptosis Through ROS/Mapks Pathway

Abstract: Background/Aims: Myocardial ischemia/reperfusion (I/R) injury remains a great challenge in clinical therapy. Tissue inhibitor of metalloproteinases 3 (TIMP3) plays a crucial role in heart physiological and pathophysiological processes. However, the effects of TIMP3 on I/R injury remain unknown. Methods: C57BL/6 mice were infected with TIMP3 adenovirus by local delivery in myocardium followed by I/R operation or doxorubicin treatment. Neonatal rat cardiomyocytes were pretreated with TIMP3 adenovirus prior to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 33 publications
(58 reference statements)
2
42
0
1
Order By: Relevance
“…ROS is massively produced in I/R injury, especially at the reperfusion phase. Several studies found that ROS is elevated in the I/R injury model, and associated with apoptosis [33,34]. We also examined the ROS level in cardiac tissue of I/R rats and supernatants of H/R H9c2 cells and found that ROS was significantly increased, which conformed with previous studies.…”
Section: Bioinformatic Analysis and Luciferase Assay In The Present Ssupporting
confidence: 89%
“…ROS is massively produced in I/R injury, especially at the reperfusion phase. Several studies found that ROS is elevated in the I/R injury model, and associated with apoptosis [33,34]. We also examined the ROS level in cardiac tissue of I/R rats and supernatants of H/R H9c2 cells and found that ROS was significantly increased, which conformed with previous studies.…”
Section: Bioinformatic Analysis and Luciferase Assay In The Present Ssupporting
confidence: 89%
“…Scholars also revealed that lncRNAs have been discovered to be implicated in myocardial I/R injury. Apoptosis has been reported to be induced under hypoxic stress in ischemic injury [21], and lncRNA UCA1 can regulate cardiomyocyte apoptosis in myocardial I/R injury [15]. LncRNA CARL is found to inhibit anoxia-induced cardiomyocyte apoptosis [22] and suppression of lncRNA TTTY15 can protect against hypoxia-induced cardiomyocyte apoptosis [23], suggesting the latent role of these lncRNAs in IMI.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a process of programmed cell death that is activated under hypoxic stress in ischemic injury and during the production of ROS in reperfusion injury [84, 85]. Apoptotic mechanisms are divided into two major pathways: the extrinsic-and intrinsic pathways.…”
Section: Apoptosis and Mitoptosismentioning
confidence: 99%